The Role of Political Communication in Shaping Public Opinion: a Comparative Analysis of Traditional and Digital Media - Daud, Rollyn Sofyan (Journal of Public Representative and Society Provision, 2021)
The purpose of this research is to identify the changes that have occurred in the role of conventional and digital media in relation to public opinion and political participation with emphasis on the comparative efficaciousness of both categories. Employing a qualitative research design, the study employs interviews, focus groups, and content analysis to determine how different categorisations experience and interact with the various types of media. The meta-synthesis shows the breakdown of trust in their generations, where the older participants trusted the traditional media established as credible while the young participants were more careful while relating with the new digital media. Another important aspect of the study is the aspect of framing in the media narratives and the issue of misinformation or disinformation that has become virtually rife especially on social media. In addition, the study knits together by drawing the link between media consumption and politicisation and how in the current age of the digital media there is both enhancement of participation and a problem of conspicuous participation. In light of the findings, the study calls for an improvement of digital literacy and coming up with measures to effectively deal with fake news; The study also notes the need to engage in informed and healthy discourse in the digital environment.